Device-Independent Quantum Key Distribution Over Long-Distance Fiber Networks Using Entanglement Swapping Architectures - Ava Lee; Marcus Tan; Baasandorj Gankhuyag (Yayasan Adra Karima Hubbi, 2025)
Quantum Key Distribution (QKD) has emerged as a powerful solution for secure communication, relying on the principles of quantum mechanics to guarantee the security of transmitted keys. However, traditional QKD protocols are dependent on the trustworthiness of the devices used, which introduces vulnerabilities. Device-independent quantum key distribution (DI-QKD) eliminates this dependency, offering a higher level of security. This research explores the use of DI-QKD over long-distance fiber networks by incorporating entanglement swapping architectures to extend the reach and enhance the security of quantum key distribution systems. The objective of this study is to evaluate the feasibility of DI-QKD over long-distance fiber-optic networks, employing entanglement swapping as a means to mitigate photon loss and noise over extended distances. The research employs both theoretical modeling and experimental validation, simulating long-distance fiber links with quantum repeaters and entanglement swapping nodes. The results demonstrate that entanglement swapping significantly extends the distance over which secure DI-QKD can be achieved, maintaining low quantum bit error rates (QBER) and high key generation rates even at distances of 200 km. The findings confirm that DI-QKD is feasible over practical fiber networks, and entanglement swapping is a key enabler for long-distance secure quantum communication.